The two nations of black America - Cross, June.; Gates, Henry Louis, Jr.; West, Cornel; Bond, Julian, 1940-2015.; Karenga, Maulana; Cleaver, Eldridge, 1935-1998.; Cleaver, Kathleen; Davis, Angela Y. (Angela Yvonne), 1944-; Wilson, William J., 1935-; Jackson, Jesse, 1941-; Jones, Quincy, 1933-2024; Sykes, David; et al. ([Alexandria, Va.] : Distributed by PBS Home Video, 2008)
There is a growing economic divide in black America. Today, America's black middle class is the largest in its history, yet roughly one-third of black America continues to live in poverty. This film measures the economic and social success of the civil rights movement and the gap between middle class and poor African-Americans through interviews with noted Afro-Americans and historical film footage.
DVD, full screen; NTSC.
Closed-captioned.
Commentary: Cornel West, Julian Bond, Maulana Karenga, Eldridge Cleaver, Kathleen Cleaver, Angela Davis, William Julius Wilson, Jesse Jackson, Quincy Jones, David Sykes, Christopher Edley, Orlando Patterson ; voice of W.E.B. Doubois: Avery Brooks.
Originally presented as an episode of the television series Frontline in 1998.
Keywords: African Americans -- Economic conditions; African Americans -- Social conditions; Social classes -- United States; African Americans -- Race identity; Black Panther Party -- History; Ethnicity -- Social aspects -- United States; Urban poor -- United States; Poverty -- United States; March on Washington for Jobs and Freedom, Washington, D. C., 1963.; Civil rights movements -- United States -- Influence; African Americans -- Economic conditions; African Americans -- Social conditions; Social classes -- United States; Documentary television programs; Video recordings for the hearing impaired; Documentary -- Television